Two new Neanurid Collembola, Paranura and Yuukianura (Neanuridae: Neanurinae) from Japan, with a checklist of species and key to the Japanese genera of Neanurinae - Kasai, Hiro; Ohgita, Shotaro; Osaki, Kazutaka; Murase, Shunya (Zootaxa, 2024)
We describe and illustrate two new species of Neanurinae, Paranura ezoensis sp. nov. and Yuukianura kikaiensis sp. nov., collected from Hokkaido and Kikai Island, southwest Japan, respectively. The general morphology of P. ezoensis sp. nov. resembles P. conjuncta Smolis & Deharveng, 2015, however, it differs by its 12 chaetae on Ant. II, labrum chaetotaxy 4/2,4, tubercles Di on Abd. V separated from each other, and 16 ventral chaetae Ve on Abd. Vl. Y. kikaiensis sp. nov. is most similar to Y. pacifica (Yosii, 1971). However, this new species is clearly distinguishable by its long macrochaetae, chaeta Ocm longer than chaeta Ocp and Oca on the head, Abd. I–IV with 2 ordinary chaetae Di, Th. II–III with 4 ordinary chaetae De, and ventral fringed lamella on the maxilla as long as dorsal claw-like lamella. Y. pacifica is a halobiont species, whereas Y. kikaiensis sp. nov. is found in forests. We provided keys to species in Paranura with three pairs of eyes and to all species of the genus Yuukianura. Furthermore, a checklist of all Japanese Neanurinae species and an identification key for all Japanese genera within the subfamily Neanurinae are included.